‘Shari’ah’ based banking and green financing: evidence from Bangladesh / Mohammad Nazim Uddin. - Uddin, Mohammad Nazim (Universiti Teknologi Mara Selangor, 2016)
Environmental protection and sustainability is the part of Islamic finance to ensure the fulfilment and establishments of spirit of Islamic tenants. The need to care for the environment and the forms of life that Allah has created on this earth that includes proper usage of natural resources (Al-Fajr: 11-14). Green finance involves the allocation of funds to the environmental friendly projects that help the mankind from any harmful and compliance to the ‘Shari’ah’ rules. The main purpose of the study is to examine the role of ‘Shar’ah’ based banking on green financing in Bangladesh. The study has used the structural questionnaire for primary data that includes various dimensions on green financing of ‘Shari’ah’ based banking in Bangladesh. The study has also used secondary data relevant to articles, journals, books, and conference papers for theoretical development. In order to validate the findings, the necessary statistical measures include 5 point Likert scale, mean, and rank are used in the study. The study revealed that ‘Shari,ah’ based banking have made significant contribution in green financing that promote the preservation of natural resources and the need to respect all living things. The study seems to carry an enormous academic value since a few studies have been undertaken in this area. The results could be useful to the government, Bangladesh Bank, NGOS, Donors, international agency, World Bank, IMF, Academic researchers and national policy makers who have been making endeavor to save the environment in developing countries as well as Bangladesh as a whole.